Biallelic Loss of Function of SORL1 in an Early Onset Alzheimer's Disease Patient. - Le Guennec, Kilan; Tubeuf, Hélène; Hannequin, Didier; Wallon, David; Quenez, Olivier; Rousseau, Stéphane; Richard, Anne-Claire; Deleuze, Jean-François; Boland, Anne; Frebourg, Thierry; Gaildrat, Pascaline; Campion, Dominique; et al. (J Alzheimers Dis, 2018)
Heterozygous SORL1 protein truncating variants (PTV) are a strong risk factor for early-onset Alzheimer's disease (EOAD). In case control studies performed at the genome-wide level, PTV definition is usually straightforward. Regarding splice site variants, only those affecting canonical sites are typically included. Some other variants, not annotated as PTV, could, however, affect splicing and hence result in a loss of SORL1 function. We took advantage of the whole exome sequencing data from the 9/484 patients with a previously reported SORL1 PTV in the French EOAD series and searched for a second variant which may affect splicing and eventually result in more than 50% loss of function overall. We found that one patient, known to carry a variant predicted to disrupt the canonical 5' splice site of exon 8, also carried a second novel intronic variant predicted to affect SORL1 splicing of exon 29. Segregation analysis showed that the second variant was located in trans from the known PTV. We performed ex vivo minigene splicing assays and showed that both variants led to the generation of transcripts containing a premature stop codon. This is therefore the first evidence of a human carrying biallelic SORL1 PTV. This patient had a family history of dementia in both maternal and paternal lineages with later ages of onset than the proband himself. However, his 55 years age at onset was in the same ranges as previously published SORL1 heterozygous PTV carriers. This suggests that biallelic loss of SORL1 function is an extremely rare event that was not associated with a dramatically earlier age at onset than heterozygous SORL1 loss-of-function variant carriers, in this single patient.
Keywords: Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Risk Factors

APP Mutations in Cerebral Amyloid Angiopathy with or without Cortical Calcifications: Report of Three Families and a Literature Review. - Sellal, François; Wallon, David; Martinez-Almoyna, Laurent; Marelli, Cecilia; Dhar, Abhinav; Oesterlé, Héléne; Rovelet-Lecrux, Anne; Rousseau, Stéphane; Kourkoulis, Christina E; Rosand, Jon; DiPucchio, Zora Y; Frosch, Matthew; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Specific APP mutations cause cerebral amyloid angiopathy (CAA) with or without Alzheimer's disease (AD). OBJECTIVE: We aimed at reporting APP mutations associated with CAA, describe the clinical, cerebrospinal fluid AD biomarkers, and neuroimaging features, and compare them with the data from the literature. METHODS: We performed a retrospective study in two French genetics laboratories by gathering all clinical and neuroimaging data from patients referred for a genetic diagnosis of CAA with an age of onset before 66 years and fulfilling the other Boston revised criteria. We studied the segregation of mutations in families and performed a comprehensive literature review of all cases reported with the same APP mutation. RESULTS: We screened APP in 61 unrelated French patients. Three mutations, located in the Aβ coding region, were detected in five patients from three families: p.Ala692Gly (Flemish), p.Glu693Lys (Italian), and p.Asp694Asn (Iowa). Patients exhibited CAA and progressive cognitive impairment associated with cortical calcifications in the Iowa and Italian mutation carriers, but not the patient carrying the Flemish mutation. CONCLUSIONS: This is the first evidence of cortical calcification in patients with an APP mutation other than the Iowa mutation. We discuss the radiological, cerebrospinal fluid, and clinical phenotype of patients carrying these mutations in the literature.